Edukasi Obat Batuk oleh Dosen Farmasi pada Warga yang Berkunjung di Apotek Byel Farma - Teodhora; Ainun Wulandari; Amelia Febriani; Vilya Syafriana; Ika Maruya Kusuma (LP3M Universitas Putra Bangsa, 2024)
Coughing is a condition where an individual expels air suddenly from the thoracic cavity through the epiglottis and mouth. Coughs are commonly accompanied by phlegm or can be dry. Cough-related illnesses are frequently experienced by individuals of all ages, including adults and children. Conducting educational activities on the use of cough medicine is an essential effort to enhance public understanding of health. This educational initiative was carried out at Apotek Byel Farma to provide comprehensive and practical information on the appropriate use of cough medicine. The objective of this activity is to improve public knowledge and understanding of the types of cough medicine, correct usage, and the importance of following usage instructions. The methods employed include organizing educational sessions, question-and-answer sessions, and distributing educational materials. Participants involved in this activity comprised the general public visiting Apotek Byel Farma. The results of this activity indicate a significant increase in participants' knowledge and understanding of cough medicine usage, as well as awareness of the importance of consulting healthcare professionals. In conclusion, this educational campaign has successfully made a positive contribution to increasing public health awareness regarding the correct use of cough medicine.